Predictive value of plasma copeptin level for diagnosis and mortality of pulmonary embolism - Ozmen,Caglar (2020)
SUMMARY OBJECTIVE: Early diagnosis and risk stratification may provide a better prognosis in pulmonary embolism (PE). Copeptin has emerged as a valuable predictive biomarker in various cardiovascular diseases. The aim of this study was to determine the levels of copeptin in patients with acute PE and to evaluate its relationship with disease severity and PE-related death. METHODS: Fifty-four patients and 60 healthy individuals were included in this study. Copeptin concentrations and right ventricular dysfunction were analyzed. The correlation between copeptin levels and hemodynamic and echocardiographic parameters was examined. After these first measurements, patients were evaluated with PE-related mortality at the one-year follow-up. RESULTS: The copeptin levels were higher in PE patients than in the control group (8.3 ng/mL vs 3.8 ng/mL, p<0.001). Copeptin levels were found to be significantly higher in patients with PE-related death and right ventricular dysfunction (10.2 vs 7.5 ng/ml, p=0.001; 10.5 vs 7.5 ng/ml, p=0.002, respectively). When the cut-off value of copeptin was ≥5.85, its sensitivity and specificity for predicting PE were 71.9% and 85.0%, respectively (AUC=0.762, 95% CI=0.635-0.889, p<0.001). CONCLUSIONS: The copeptin measurement had moderate sensitivity and specificity in predicting the diagnosis of PE, and the copeptin level was significantly higher in patients with PE-related death at the one-year follow-up. Copeptin may be a useful new biomarker in predicting diagnosis, risk stratification, and prognosis of PE.